ANALISIS KAJIAN FEMINISME DALAM NOVEL BERJUDUL “JANGAN SALAHKAN AKU SELINGKUH” KARYA RIFANI APRIL - Rahma Aulia, Putri; Nurjamin, Asep; Kulsum, Umi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Analysis of Feminism Studies in the Novel entitled “Don’t Blame Me for Cheating” by Rifani April. The aim of this research is to find out the study of feminism contained in the novel ‘Don’t Blame Me for Cheating’ by Rifani April which is interesting to study so that it can be used as a message by researchers and readers. The method used by the researcher is a qualitative descriptive method and the research technique used is a qualitative analysis technique, in the form of quotation and interpretation data from female characters in the novel ‘Don’t Blame Me for Cheating’ by Rifani April. Based on the results of the analysis, the results of the research showed that there was one female figure who was studied regarding feminism from a Marxist perspective, namely the wife (Anna), who was full of love and attention to her husband (Dimas) for many years but was instead rewarded with painful betrayal. Shows how her husband systematically oppresses and abuses Anna, both verbally and emotionally. So Anna starts having an affair again with her old friend Reyhan with the aim of revenge so that Dimas feels what Anna feels. The conclusion that can be obtained from this research is the study of feminism carried out by husbands towards wives, such as belittling their feelings and controlling them, which leads to infidelity, injustice, oppression, and women’s psychological image rights in terms of reproduction. This gives rise to feelings of revenge carried out by the wife against her husband. To have an affair so that the husband is deterred from the behavior he has carried out during the marriage.